Temporally sensitive neural measures of inhibition in preschool children across a spectrum of irritability. Issue 2 (17th October 2018) - Deveney, Christen M.; Briggs‐Gowan, Margaret J.; Pagliaccio, David; Estabrook, Christopher R.; Zobel, Elvira; Burns, James L.; Norton, Elizabeth S.; Pine, Daniel S.; Brotman, Melissa A.; Leibenluft, Ellen; Wakschlag, Lauren S.
Abstract: Irritability is a prominent feature of chronic mental disorders and a developmental marker of their early emergence. The most salient feature of irritability in early childhood is temper tantrums. While temper tantrums are normative in young children, they can be clinically concerning when they are dysregulated, very frequent, and/or occur in unexpected contexts. The present study uses behavioral and event‐related brain potential (ERP) measures to characterize the relationship between irritability and neural markers of response inhibition in very young children. Forty‐six children (ages 4–7 years) completed a go/no‐go task under nonfrustrating and frustrating conditions. ERPs elicited by go and no‐go stimuli were examined as a function of frustration condition and irritability, operationalized via the well‐validated Temper Loss scale of the Multidimensional Assessment Profile of Disruptive Behavior (MAP‐DB). Higher Temper Loss scores were associated with larger N2no‐go amplitudes and reduced no‐go accuracy during frustration. This suggests that higher levels of irritability corresponded with increased conflict monitoring and poorer task performance during frustration. These findings add to a developing literature identifying the neurocognitive markers of varying levels of irritability in young children.